Correlating Maternal BMI and Infant Birth Weight: An Analytical Study with Insights from Gujarat, India - Kumar Lal, Akash; Pawar, Jai; Soni, Sandeep; Naik, Santosh (Journal of Neonatal Surgery, 2025)
This study investigates the correlation between maternal Body Mass Index (BMI) and infant birth weight in Gujarat, India, focusing on rural areas near the Dahej Industrial Area in Bharuch district. Low birth weight (LBW) and preterm births are significant public health concerns in India, contributing to neonatal mortality, developmental delays, and higher morbidity risks. Despite improvements in maternal and child health, 18.2% of infants in India are born with LBW, with Gujarat showing a similar rate of 17.5%. Undernutrition, indicated by low maternal BMI, is a key factor influencing LBW. With 22.9% of Indian women of reproductive age underweight, and 20% in Gujarat, the study highlights the need to explore maternal nutritional status as a determinant of birth outcomes. Utilizing primary data from rural Gujarat and secondary data from national health surveys, this research examines how maternal BMI correlates with birth weight, preterm deliveries, and delivery methods. The findings aim to guide public health interventions focused on improving maternal nutrition and neonatal health. Deepak Foundation’s healthcare initiatives in Dahej, aimed at addressing these challenges, provide a crucial context for understanding the impact of industrialization on healthcare access in vulnerable communities.